'Borono-lectin' based engineering as a versatile platform for biomedical applications. Issue 1 (31st December 2018) - Matsumoto, Akira; Miyahara, Yuji
Abstract: Boronic acids are well known for their ability to reversibly interact with the diol groups, a common motif of biomolecules including sugars and ribose. Due to their ability to interact with carbohydrates, they can be regarded as synthetic mimics of lectins, termed 'borono-lectins'. The borono-lectins can be tailored to elicit a broad profile of binding strength and specificity. This special property has been translated into many creative biomedical applications in a way interactive with biology. This review provides a brief overview of recent efforts of polymeric materials-based engineering taking advantage of such virtue of 'borono-lectins' chemistry, related to the field of biomaterials and drug delivery applications. Abstract :